Epidemiology of Non-Infectocontagious Neurological Diseases in childhood in a Hospital in Serra Catarinense in 2014 (Research, Society and Development, 2020)
Objective: to define the epidemiological profile of non-infectious and contagious neurological diseases, in a medium-sized hospital in Serra Catarinense, in patients aged zero to sixteen years. Method: cross-sectional, retrospective study of a medium-sized tertiary institution in Serra Catarinense, where hospitalizations in 2014 were evaluated, using the DataSUS database, listing the epidemiological data available for non-infectious and contagious neuropediatric diseases, up to sixteen years old. Results: a total of 1,876 patients admitted to the studied institution were evaluated. With a total of 80 hospitalizations with neurological diagnoses that are not infectious, totaling 328 days of hospitalization, with an average cost of R $ 1,027.03 per hospitalization. With a greater number of hospitalizations in males (1.5: 1). The most prevalent age was between 1-4 years with 28 hospitalizations, corresponding to 35% of the total hospitalizations. The main cause of hospitalization was epilepsy (66%), with prevalence between one and four years (43.3%), among women (57%). Expenses during hospitalizations are lower in hospitalizations for epilepsy with an average of $ 283.43 and an average length of stay of 3.3 days. Conclusion: the most prevalent disease among hospitalizations was epilepsy, where the most affected age group was between zero and four years of age, with low cost and a short hospital stay, which proved to be positive. The work in this area is scarce, requiring more studies in the scope of the epidemiology of non-infectious and contagious neurological diseases in childhood.